Development of de-novo transcriptome assembly and SSRs in allohexaploid Brassica with functional annotations and identification of heat-shock proteins for thermotolerance - Singh, Kaushal Pratap; Kumari, Preetesh; Yadava, Devendra Kumar (Frontiers in Genetics, 2022)
Crop Brassicas contain monogenomic and digenomic species, with no evidence of a trigenomic Brassica in nature. Through somatic fusion (Sinapis alba + B. juncea), a novel allohexaploid trigenomic Brassica (H1 = AABBSS; 2n = 60) was produced and used for transcriptome analysis to uncover genes for thermotolerance, annotations, and microsatellite markers for future molecular breeding. Illumina Novaseq6000 generated a total of 76,055,546 paired-end raw reads, which were used for de-novo assembly, resulting in the development of 486,066 transcripts. A total of 133,167 coding DNA sequences (CDSs) were predicted from transcripts with a mean length of 507.12 bp and 46.15 percent GC content. The BLASTX search of CDSs against public protein databases showed a maximum of 126,131 (94.72%) and a minimum of 29810 (22.39%) positive hits. Furthermore, 953,773 Gene Ontology (GO) terms were found in 77,613 (58.28 percent) CDSs, which were divided into biological processes (49.06 percent), cellular components (31.67 percent), and molecular functions (19.27 percent ). CDSs were assigned to 144 pathways by a pathway study using the KEGG database, and 1551 pathways by a similar analysis using the Reactome database. Further investigation led to the discovery of genes encoding over 2000 heat shock proteins (HSPs). The discovery of a large number of HSPs in allohexaploid Brassica validated our earlier findings for heat tolerance at seed maturity. A total of 15,736 SSRs were found in 13,595 CDSs, with an average of one SSR per 4.29 kb length and an SSR frequency of 11.82 percent. The first transcriptome assembly of a meiotically stable allohexaploid Brassica was given in this paper, along with functional annotations and the presence of SSRs, which could aid future genetic and genomic studies.